THE FORECAST OF THE POPULATION OF THE ORENBURG REGION IN THE CONTEXT OF URBAN AND RURAL AREAS BY THE METHOD OF «ADVANCING AGES» - Julia R. Yuzaeva (Статистика и экономика, 2016)
The article gives a forecasting of population of the Orenburg region in a sectionof city and rural areas by the «advancing ages» on 2017 and 2022. Based onforecast data calculated the coefﬁ cients of aging, longevity. Considered the types of age structure of the population.